Differential expression and prediction of function of lncRNAs in the ovaries of low and high fecundity Hanper sheep. Issue 4 (27th January 2021) - Liu, Aiju; Liu, Menghe; Li, Yuexin; Chen, Xiaoyong; Zhang, Limeng; Tian, Shujun
Contents: Litter size is an important trait that determines the production efficiency of sheep bred for meat. Its detailed investigation can reveal the molecular mechanisms that control the fecundity of sheep and possibly accelerate the breeding process of new varieties of sheep that have high prolificacy. Long non‐coding RNAs (lncRNAs) have proven to be an important factor in the regulation of follicular development. However, the mechanisms by which lncRNAs regulate litter size in sheep remain unclear. In the present study, ovarian tissues from the follicular (F) or luteal phase (L) of Hanper sheep that were either monotocous (M) or polytocous (P; FM, FP, LM and LP groups) were collected and sequenced to identify differentially expressed lncRNAs and predict their function. The results indicate that the number of up‐ and down‐regulated lncRNAs in the follicular phase (FM vs. FP) was 95 and 111 and 109 and 49, respectively, in the luteal phase (LM vs. LP). The functional enrichment of the different lncRNAs coexpressed with mRNA was analysed. The results demonstrated that the KISS1‐GnRH‐LH/FSH‐E2 and EGF‐EGFR‐RAS‐PI3K signalling pathways promoted the initiation of the primordial period, follicular development and ovulation in the follicular phase (FM vs. FP). During the luteal phase (LM vs. LP), the production and development of the corpus luteum in ewes was influenced by the KITLG‐KIT/FGF‐FGFR/HGF‐MET‐RAS‐ERK signalling pathway. STEM clustering functional enrichment analysis of the differentially expressed lncRNAs indicated that profile11 was principally enriched in the Cytokine‐Jak‐STAT, PDGF‐PDGFR‐PI3K and KITLG‐KIT‐RAS‐ERK signalling pathways. By analysis of the differential expression of the lncRNAs and their expression in each group, lncRNAs Xist (loc101112291) and Gtl2 (loc101123329) were found to be highly expressed, suggesting that regulation of follicular development was mediated through methylation processes.